Ways for Limit Transistor Voltage in Quasi-Resonant Converter - Sakalauskas, S. (Elektronika ir Elektrotechnika, 2000)
Because of necessity for inexpensive solid state laser’s pumping systems for continuous-wave arc lamps power supplies without galvanic insulation from main power there were done initial engineering calculations of traditional converters (voltage-down or Cook) equipped with impulse width modulation. Final results were non-acceptable. In this case was done a research of zero voltage switched (ZVS) quasi-resonant buck converter. The main disadvantage of the converter (when connecting to rectified 3-phase mains power) is voltage on the power transistor is too high – up to 2 times higher than maximal amplitude of the mains power and it’s proportional to output current. The research includes schemotechnical solutions, which provide to lower dependence of the voltage on the power transistor from converter output current. Experimental research of improved quasi-resonant are presented in the research material.